PENGGUNAAN PASIR BESI DARI KULON PROGO DENGAN BERAT JENIS 4,311 UNTUK MORTAR PERISAI RADIASI SINAR GAMMA - Putra, Hendra; Satyarno, Iman; Wijatna, Agus Budhie (Civil Engineering Forum Teknik Sipil, 2008)
The radiation effects of radiology and x-rays equipments do not only give excellent benefit for human, but also harmful effect at the same time. Protecting people form the radiation is an important aspect to control such harmful effect. Hence every nuclear installation and radiology unit must pay attention on protecting surrounding people from the radiation. Lead is commonly used as component of shield, but the use of lead requires special work and energy. In economical aspects, the cost of such effort is relatively expensive, but in workability aspects, the application of iron sand mortar can be used as alternative material to protect from radiation. This study assessed gamma radiation absorption on mortar cube sample with dimension of 15 x 15 cm and thickness variation of 1 cm to 15 cm. Mortar ingredient consisted of iron sand, cements and water, with cements - iron sand volume ratio of 1 : 6. Water cement ratio was determined at 0,4 and the gamma radiant energy applied were Iodine-131 (131I) denergi 284,00 keVs, 364,00 keVs, 637,00 keVs and Caesium-137 (137Cs) dissociation energy of diatomic 662,00 keV. Physical test gradation conducted to iron sand from Congot beach Kulonprogo regency of Daerah Istimewa Yogyakarta Province, showed specific gravity of 4,331 with, Ssd specific gravity of 4,330, unit weight of 2,554 gr/cmÂ³, water absorbency 0,442%, and grain finest modulus of 1,33, which was categorized as zone IV (smooth gradation). Compressive strength and specific gravity of Iron sand mortar at 28 days reached 7,92 MPa and 2,59 respectively. Especially, specific gravity was heavier than ordinary cements mortar with average value ranged from 1,80 - 2,20. Coefficient linear magnitude attenuation (Î¼) of iron sand mortar at radiation energy 284 keVs, 364 keVs, 637 keVs and 662 keVs were 0,2816 cm-1, 0,2253 cm-1, 0,1297 cm-1 and 0,1003 cm-1 respectively. Based on these relation, the line equation obtained was y = 0,5631e(-0025X).